Perubahan Sosial dalam Novel Di Kaki Bukit Cibalak Karya Ahmad Tohari - Dara Windiyarti (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2006)
Abstract This article is proposed to study social problem which is reflected in novel Di Kaki Bukit Cibalak by Ahmad Tohari. The study employs close reading method based on Marxist theory. The result of the study shows that explicitly the novel reveal social problems caused by economic factor. Social conflict. Social conflict appears when corruption is committed by the village officers which lead to the oppressed classes. The conflict apparently dominates the story which involves the character’s attitude, in this way this novel intensively tries to articulate the struggle of the oppressed to make oppressor aware that change is urgently needed. The social change must be performed to fulfill the desire of the oppressed, that is classless society Key words: social change, social class, oppressor, oppressed.